Comparing Diagnostic Tools in Personality Disorders - Emel AKGUN AKTAS; Seher Olga GURIZ; Akfer KARAOGLAN KAHILOGULLARI; Guler ALPASLAN; Esra CAVDAR; Aysegul DAGDEVIREN (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Personality Disorder is defined as; continually self experience and behavioral pattern which has great variations of individual cultural normal expectations. Several diagnostic tools were developed for diagnosing personality disorders. In our study consistency of different diagnostic tools used for thhe diagnosis of personality disorders were evaluated. 39 inpatients diagnosed as personality disorder from Diskapi Yildirim Beyazit Traning and Reseach Hospital were recruited into the study. Psychotic patients are excluded from the study. Sociodemographic Information Form, MMPI and PBQ scales were given all the patients. Both PBQ personality subscales and MMPI PD scales were compared with semi-structured SCID-II interview diagnoses. Findings suggest less correlation than expected. Relatively higher correlation was found between PBQ personality subscales and MMPI-PD. Most common psychiatric comorbid disorder was depression. These findings suggest that further studies are needed for the development of diagnostic tools which take the differences of self report scales and clinical evalution into consideration. Beside, the differences of the categorical and dimensional classification of personality disorders should be bear in mind in evaluation of this patient group. [JCBPR 2016; 5(1.000): 22-27]